Alive inside, dead outside: Cultural implications of the documentary Alive Inside. Issue 1 (1st July 2019) - Clements-Cortes, Amy; Futerman, Liza
This article reflects on the cultural discourse of Alzheimer's Disease (AD) that has rooted the disease in numerous metaphors preserving the unknown aspects of AD and supporting its status as a 'social death'. Through engagement with Michael Rossato-Bennett's documentary film, Alive Inside: A Story of Music and Memory, a number of scenes from the film are discussed. Through qualitative discourse analysis, we challenge the cultural discourse of AD highlighted throughout Alive Inside, and outline some cautions on the iPod project for persons with AD, in particular isolation caused by using headphones to engage with the music. While there are numerous benefits in music listening for persons across the lifespan; for an individual with AD it is important for a healthcare professional or caregiver to monitor the listening experience, and to consider sharing the music with them via speakers. This is a responsible and effective way of including music in the overall care plan for an individual with AD. Further, the benefits of music experiences can be more fully realized in many cases when they are implemented by a credentialed music therapist in working with vulnerable populations.